1992
DOI: 10.1021/j100191a007
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR study on the molecular dynamics of solid porphine-d2

Abstract: pulsed NMR techniques were used to investigate the solid-state dynamics of porphine molecules in which the central protons have been replaced by deuterons. Changes observed in the line width of the *H NMR signal suggest that, as happened to be the case with the fully protonated derivative, molecules of deuterated porphine rotate in the crystal. Variable-temperature measurements of the proton relaxation times in the rotating frame provided the activation parameters for this motion, which were found to be slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Free-base porphyrins possess two central hydrogens that may bind to any of the four inner nitrogens in the molecule. Exchange among the different possible arrangements results in a tautomeric process (Figure ) that has been extensively studied by variable-temperature solution and solid-state NMR. The latter analysis showed that crystal packing forces may disturb the equilibrium constant of the tautomerism, yielding exchange processes between nondegenerate states even in the case of symmetrically substituted molecules.…”
mentioning
confidence: 99%
“…Free-base porphyrins possess two central hydrogens that may bind to any of the four inner nitrogens in the molecule. Exchange among the different possible arrangements results in a tautomeric process (Figure ) that has been extensively studied by variable-temperature solution and solid-state NMR. The latter analysis showed that crystal packing forces may disturb the equilibrium constant of the tautomerism, yielding exchange processes between nondegenerate states even in the case of symmetrically substituted molecules.…”
mentioning
confidence: 99%
“…In free-base porphyrins the two inner hydrogens can migrate between the four central nitrogens, giving rise to two possible tautomers and therefore to a hydrogen migration process that has been extensively studied by means of solution and solid-state NMR. The latter studies revealed the presence of dynamic processes for structures that X-ray diffraction studies presented as motionless solids, a fact that can be attributed in part to the difficulties that X-ray diffraction has for localizing hydrogens . In porphycene 1 the porphyrinoid structure can also give rise to two tautomeric structures since it allows the presence of the NH exchange process 1a ⇌ 1b (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear magnetic resonance experiments can be accelerated by designing new pulse sequences or even spectrometer hardware. Examples include spatial encoding of spectral dimensions in single‐scan spectroscopy, reducing the individual measurement time by speeding up the magnetization recovery after each scan, and observing a small fraction of the frequency space as in the Hadamard spectroscopy . The approach called covariance spectroscopy produces high‐resolution spectra by transferring the high resolution in the direct dimension to the indirect dimensions, and thus reducing the sampling demands in the indirect dimensions and shortening the experiment.…”
mentioning
confidence: 99%